Kajian Konsep Termodinamika Pada Diffuser Sederhana - Siti Khairunnisa; Riska Amelza; Nurmasyitah Nurmasyitah (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
In this study the diffuser has different functions. You may already know the function of this diffuser. Diffuser Has a function to clean the air from viruses, dust, and pollution. Usually, the diffuser is mixed with essential oil to give a nice scent around the room. The purpose of this study was to examine the physics concept of the diffuser by knowing the ratio of the relationship between water volume and time, and the relationship between time and temperature in mode 1 and mode 2. the purpose of this research can be implemented. There are several stages in conducting research regarding the comparison of the relationship between volume of water and time, and the relationship of time with temperature in mode 1 and mode 2. Based on the graph above, the relationship between volume and evaporation run out using 1 minute mode, when 15 ml of evaporation run out for 35 minutes, when 25 ml evaporates for 90 minutes, when 35 ml evaporates for 120 minutes and when 45 ml of water evaporates for 240 minutes. When viewed from the correlation value R^2 = 0.9072, this shows that there is a relationship of 90.0% (accurate correlation). Furthermore, the relationship of water volume to time is obtained, when 5 ml of water evaporates for 10 minutes, when 15 ml evaporates for 25 minutes, when 25 ml evaporates for 70 minutes, when 35 ml evaporates for 35 minutes 90 minutes and when 45 ml of water evaporates for 120 minutes. In this study the diffuser has different functions. You may already know the function of this diffuser. Diffuser Has a function to clean the air from viruses, dust, and pollution. Usually, the diffuser is mixed with essential oil to give a nice scent around the room. The purpose of this study was to examine the physics concept of the diffuser by knowing the ratio of the relationship between water volume and time, and the relationship between time and temperature in mode 1 and mode 2. the purpose of this research can be implemented. There are several stages in conducting research regarding the comparison of the relationship between volume of water and time, and the relationship of time with temperature in mode 1 and mode 2. Based on the graph above, the relationship between volume and evaporation run out using 1 minute mode, when 15 ml of evaporation run out for 35 minutes, when 25 ml evaporates for 90 minutes, when 35 ml evaporates for 120 minutes and when 45 ml of water evaporates for 240 minutes. When viewed from the correlation value R^2 = 0.9072, this shows that there is a relationship of 90.0% (accurate correlation). Furthermore, the relationship of water volume to time is obtained, when 5 ml of water evaporates for 10 minutes, when 15 ml evaporates for 25 minutes, when 25 ml evaporates for 70 minutes, when 35 ml evaporates for 35 minutes 90 minutes and when 45 ml of water evaporates for 120 minutes. When viewed from the correlation value R^2 = 0.981, this shows that there is a relationship of 9.8% (very accurate correlation). While the relationship of time to temperature in mode 1 is obtained at 15 minutes with a temperature of 29.6?C, at 35 minutes the required temperature is 29.4?C at 90 minutes the required temperature is 30.2?C , at 120 minutes the required temperature is 32.9?C, at 420 minutes the required temperature is 37.9?C. When viewed from the correlation value R^2 = 0.9094, this shows that there is a relationship of 90.0% (accurate correlation). And based on the graph above in Figure 4 regarding the relationship of time to temperature in mode 1 obtained at 10 minutes with a temperature of 27.8?C, at 25 minutes the required temperature is 29.4?C at 70 minutes the required temperature is 30, 2?C , at 90 minutes the required temperature is 30.7?C, at 120 minutes the required temperature is 31.4?C. When viewed from the correlation value R^2 = 0.9067, this indicates that there is a relationship of 90.0% (accurate correlation).